Pengaruh Penggunaan Teknologi Informasi dan Kompetensi Pengguna Terhadap Kualitas Sistem Informasi Akuntansi pada Perusahaan Manufaktur di Kabupaten Bekasi - Yusril, Yusril; Sati, Indri Laras (LPPM STIE Bisnis Internasional Indonesia, 2025)
This study aims to determine: the effect of information technology utilization on the quality of accounting information systems, the influence of user competence on the quality of information systems, and the influence of the use of information technology and user competencies on the quality of accounting information systems. The population of this study were employees at manufacturing companies in Bekasi Regency. The data source used is primary data. The method used in this study is quantitative research methods through data collection techniques with questionnaires distributed to 78 employees. The data analysis technique used is SPSS with the help of SPSS V 23.0 software. The results showed that Information Technology Utilization influenced the Quality of Accounting Information Systems in manufacturing companies in Bekasi Regency. User Competence affects the Quality of Accounting Information Systems in manufacturing companies in Bekasi Regency. And the influence of the use of information technology and user competence on the quality of the accounting information system with the influence of the quality of the accounting information system is 60.40% and the remaining 39.60%.